Artificial Intelligence to Power the Future of Materials Science and Engineering. (24th March 2020) - Sha, Wuxin; Guo, Yaqing; Yuan, Qing; Tang, Shun; Zhang, Xinfang; Lu, Songfeng; Guo, Xin; Cao, Yuan-Cheng; Cheng, Shijie
Abstract : Artificial intelligence (AI) has received widespread attention over the last few decades due to its potential to increase automation and accelerate productivity. In recent years, a large number of training data, improved computing power, and advanced deep learning algorithms are conducive to the wide application of AI, including material research. The traditional trial‐and‐error method is inefficient and time‐consuming to study materials. Therefore, AI, especially machine learning, can accelerate the process by learning rules from datasets and building models to predict. This is completely different from computational chemistry where a computer is only a calculator, using hard‐coded formulas provided by human experts. Herein, the application of AI in material innovation is reviewed, including material design, performance prediction, and synthesis. The realization details of AI techniques and advantages over conventional methods are emphasized in these applications. Finally, the future development direction of AI is expounded from both algorithm and infrastructure aspects. Abstract : Herein, the basics of artificial intelligence (AI) especially machine learning are introduced. The application of AI in materials science is then reviewed, including property prediction, synthesis route planning, and processing optimization. Finally, the future development direction of AI is expounded from both hardware and software aspects.